Peningkatan Pembelajaran Melalui Media Pembelajaran Video Animasi Untuk Sekolah Dasar - Fitri Andini Al-Fatihah; Ibnu Muthi (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to (1) develop animated video learning media to improve student learning outcomes, (2) determine the feasibility of animated video learning media through teacher validation, and (3) determine the effectiveness of animated video learning media applied to class IV in Jambi City State Islamic Madrasah. The subjects in this study were 35 fourth grade students, as a test class. This reseach and development uses the Classroom Action Research Method developed by Kemmis and Mc Taggart (1992:11). The method is carried out from the first to the fourth step, namely: (1) planning, (2) action, (3) observation, and (4) reflection. The effectiveness test uses data collection techniques in the from of observation, interviews, tests, and documentation. The effectiveness of animated video media to increase motivation, attract attention, increase understanding, improve student learning outcomes, and learning objectives can be achieved as desired. Effectiveness can be seen from the scores of students’ completenss presentation results at the pre-cycle stage, the first cycle stage, then continued with the activity stages in the second cycle. The result of the study indicate that the animated video learning media is feasible to use for learning at the elementary school level. The results of the feasibility test of animated video learning media through teacher validation in operational field trials in the “Good” category. Tehere is a significant difference in the results of the presentation of students’ completeness scores between before and after using animated video learning media in the teaching and learning process.